2013
DOI: 10.1542/peds.2013-1880
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Endotracheal Ventilation to Prevent Bronchopulmonary Dysplasia: A Meta-analysis

Abstract: Avoiding Endotracheal Ventilation to Prevent Bronchopulmonary Dysplasia: A Meta-analysis abstract BACKGROUND AND OBJECTIVE: Mechanical ventilation via an endotra-cheal tube is a risk factor for bronchopulmonary dysplasia (BPD), one of the most common morbidities of very preterm infants. Our objective was to investigate the effect that strategies to avoid endotracheal mechanical ventilation (eMV) have on the incidence of BPD in preterm infants ,30 weeks' gestational age (GA). METHODS: In February 2013, we searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(182 citation statements)
references
References 80 publications
5
168
1
1
Order By: Relevance
“…26 Secondary outcomes included frequency of delivery room CPAP (goal of increasing frequency), and intubation and surfactant administration in the delivery room (goal of reducing frequency, which may help to prevent bronchopulmonary dysplasia). 27 The CPQCC data set was the source of measurement; these data are collected by trained abstractors by using standard definitions and methods. 23 Balancing measures included (1) hyperthermia (temperature .37.5°), (2) the need for epinephrine and chest compressions, and (3) pneumothorax rates.…”
Section: Study Outcomesmentioning
confidence: 99%
“…26 Secondary outcomes included frequency of delivery room CPAP (goal of increasing frequency), and intubation and surfactant administration in the delivery room (goal of reducing frequency, which may help to prevent bronchopulmonary dysplasia). 27 The CPQCC data set was the source of measurement; these data are collected by trained abstractors by using standard definitions and methods. 23 Balancing measures included (1) hyperthermia (temperature .37.5°), (2) the need for epinephrine and chest compressions, and (3) pneumothorax rates.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Some studies showed that there was no clear demonstration of a reduction of bronchopulmonary dysplasia (BPD) with the use of noninvasive ventilation [7][8][9][10]. However, recent meta-analysis made by Schmolzer [11] and Fischer [12] demonstrated that there is a statistically significant advantage in the use of non-invasive ventilation regarding death and BPD.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 The results of randomized controlled trials (RCTs), considered both individually [3][4][5] and collectively, 6,7 suggest that initiation of nasal continuous positive airway pressure (CPAP) is at least as good, if not better than early intubation and exogenous surfactant therapy. These findings have recently led to an American Academy of Pediatrics recommendation that application of CPAP at the outset should be considered as a worthy alternative to intubation, including at the lower extremes of gestation.…”
mentioning
confidence: 99%